Геология и нефтегазоносность Днепровско-Донецкой впадины. Стратиграфия [монография] - Айзенберг Д. Е.; Берченко О. И.; Бражников Н. Е.; Вдовенко М. В.; Винниченко Л. В.; Винниченко Л. Г.; Воронова М. А.; Высочанский И. В.; Горак С. В.; Горбунов В. С.; Зосимович В. Ю.; Иванников А. В.; et al. (Киев, Наукова думка, 1988)
Авт. указаны на обороте тит. л.